(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes the definitions of domestic and foreign scientists regarding the concept of professional competence, competency, professional competence of a chemistry teacher, presents the authorʼs definition of the professional competence of a chemistry teacher of a higher educational institution, the definition methodology presents the professional competence of a chemistry teacher, and highlights the pedagogical and psychological foundations for its improvement.